Numerical simulation of heat transfer and friction in non-uniform wall roughness lattice with different roughness element shapes. (November 2015) - Xiao, Hongguang; Chen, Wenzhen; Yan, Binghuo
Highlights: The non-uniform wall roughness lattices with different roughness element shapes are studied. The maximum heat transfer enhancement increases about 2.6–6 times. The friction loss increases 4.5–10 times in the same lattice. The non-uniform wall roughness lattice with the hemisphere particle roughness is recommended. Abstract: The heat transfer and friction characteristics in non-uniform wall roughness lattice are simulated using unsteady Reynolds-averaged Navier–Stokes (URANS) method with the Reynolds stress model (RSM). The influences of four different roughness element shapes on the performance of new lattice are researched. It is revealed that the quasi-periodic large scale vortex structure (QPLSVS) is enhanced after the roughness elements are introduced. In the range of Re studied in this work (5000 < Re < 85, 000), the lattice with the square rib roughness has the maximum friction factors and heat transfer coefficients. The order of heat transfer enhancement in the new lattice is about 2.6–6 times larger than that in the traditional lattice. However, the increase of the friction loss in the new lattice is 4.5–10 times larger than that in the traditional lattice. Considering the effects of flow resistance and heat transfer, a new non-uniform wall roughness lattice with the hemisphere particle roughness is recommended.